The complete guide to postnatal fitness - DiFiore, Judy (Bloomsbury Publishing PLC, 2010)
The third edition of this Complete Guide. A guide for new mums, fitness leaders and physios on how to regain fitness following the birth of a baby, including lots of exercises, advice, and all relevant anatomy and physiology. Clearly explained, fully updated and packed with exercises. Includes new guidance and up to date references, and all illustrations replaced with new photographs.